Inoculation with Pseudomonas spp. in Solanum lycopersicum increases yield and fruit quality under nutrient shortage conditions - Patricia Torres-Solórzano; Homero Reyes-De la Cruz; Josué Altamirano-Hernández; Lourdes Macías-Rodríguez; Jesús Campos-García; Alfonso Luna-Cruz (PeerJ)
Background Greenhouse tomato cultivation has experienced significant growth in recent years. However, this production system requires high fertilization levels, relying mainly on synthetic agro-inputs. While their use meets the crop’s nutritional demand, they present major limitations. Excessive application reduces absorption efficiency, increases soil salinity, and can contaminate water sources. Additionally, rising global fertilizer costs have made it necessary to seek efficient alternatives with lower contamination risks. In this context, plant growth-promoting rhizobacteria (PGPR) are a viable option to reduce inorganic fertilizer use. These microorganisms enhance nutrient availability and stimulate crop development. For this reason, the ability of five Pseudomonas strains to reduce nitrogen, phosphorus, and calcium-based fertilizers by up to 50% was evaluated in ‘El Cid F1’ tomato cultivation under a hydroponic greenhouse production system. Their performance was analyzed both individually and in consortium. Methods Preliminary in vitro tests demonstrated that Pseudomonas sp. isolates C13, C14, and C15, Pseudomonas fluorescens C30, and P. putida ACJ14, both individually and consortium could fix nitrogen, solubilize phosphate and biosynthesize indole-3-acetic acid. Greenhouse trials revealed the potential of the Pseudomonas spp. isolates to stimulate vegetative growth while improving fruit quality parameters including firmness, total soluble solids, titratable acidity, and lycopene concentration. Results The P. putida ACJ14 and Pseudomonas sp. C14 isolates significantly increased fruit yield by 54% and 73%, respectively. Lycopene content increased to 132.9 mg/kg of fruit with Pseudomonas ACJ14 and 130.22 mg/kg of fruit with Pseudomonas sp. C14. The consortium showed no significant difference in any parameters compared to individual isolates. All isolates demonstrated rhizosphere persistence for 30 days post-root inoculation. Conclusions The results position Pseudomonas spp. isolates C13, C14, C15, P. fluorescens C30, and P. putida ACJ14 as sustainable PGPR alternatives enabling 50% reduction of nitrogen, phosphorus, and calcium fertilization in greenhouse tomatoes. The strain Pseudomonas sp. C14 emerged as particularly effective, demonstrating the highest nitrogen fixation capacity, second highest IAA production, and superior performance in seed germination rates, fruit firmness, and lycopene enhancement.